Menyoal Kembali Partikel Ta dalam Bahasa Jawa Kuno - Dwi Puspitorini (Perpustakaan Nasional RI, 2022)
Old Javanese is known as a language that has a predicate clause pattern (V) preceding the subject (S). Usually, there is a particle ta or its variation between the predicate-subject sequences (V-ta-S). Besides the V-S pattern, the S-V pattern is also found. In this paper, it is shown that the clause pattern in Old Javanese is triggered by the importance of forming a narrative discourse. Particle ta and several other syntactic elements have a role in shaping narrative discourse. Other syntactic elements are the definition of nouns, arguments in the form of nouns (NP) or pronouns, and affective-passive verbs.The source of the data I use for this study is the Old Javanese parwa text, namely Adiparwa edited by Juynboll (1906). According to Molen (2010, 396), parwa is a literary product in itself. Parwa must be viewed as a literary work, just like kakawin. There is a clear story structure aided by lexical, grammatical, and literary structuring tools. In this study, the grammatical elements used for the purpose of building the story are shown.